Analysis of Platform Dynamic Response With a 3 × 3 Mooring System for the DTU 10 MW Wind Turbine Based on OpenFAST - Hao Zhang; Mocheng Yi; Dazhao Sun; Zhipeng Chen (Shock and Vibration)
A novel 3 × 3 mooring system was designed for the DTU 10 MW wind turbine based on the floating platform OOStar. This new mooring system was compared with the original mooring system using OpenFAST. Dynamic response analyses were conducted considering different hawse pipe heights and scenarios of maximum tension mooring line breakage. The results indicated that the novel 3 × 3 mooring system significantly improved stability compared to the 3 × 1 mooring system. This conclusion was drawn by comparing the maximum tension in mooring lines, surge, heave, pitch, and the fore-aft acceleration of the nacelle between the two mooring configurations.